Experimentally induced antipredator responses are mediated by social and environmental factors. (12th April 2019) - Groenewoud, Frank; Kingma, Sjouke A; Bebbington, Kat; Richardson, David S; Komdeur, Jan
Abstract: Nest predation is a common cause of reproductive failure for many bird species, and various antipredator defense behaviors have evolved to reduce the risk of nest predation. However, trade-offs between current reproductive duties and future reproduction often limit the parent's ability to respond to nest predation risk. Individual responses to experimentally increased nest predation risk can give insights into these trade-offs. Here, we investigate whether social and ecological factors affect individual responses to predation risk by experimentally manipulating the risk of nest predation using taxidermic mounts in the cooperative breeding Seychelles warbler ( Acrocephalus sechellensis ). Our results show that dominant females, but not males, alarm called more often when they confront a nest predator model alone than when they do so with a partner, and that individuals that confront a predator together attacked more than those that did so alone. Dominant males increased their antipredator defense by spending more time nest guarding after a presentation with a nest predator, compared with a nonpredator control, but no such effect was found for females, who did not increase the time spent incubating. In contrast to incubation by females, nest guarding responses by dominant males depended on the presence of other group members and food availability. These results suggest that while female investment in incubation is always high and not dependent on social and ecological conditions, males have a lower initial investment, which allows them to respond to sudden changes in nest predation risk. Abstract : Parental investment in antipredator defense depends on its relative costs and benefits. By experimentally manipulating nest predation risk in the Seychelles warbler, we show that sex-specific antipredator defenses are modified by social and ecological factors. Females show the highest investment in the nest, while males invest less, enabling them to increase their investment when predation risk increases.